Esophageal Bougienage for Management of Lodged Esophageal Coins: Safe, Effective, Efficient, and Underused. Issue 11 (29th November 2022) - Warner, Tessa N.; Genereux, Madeline; Price, Amanda B.; Titus, M. Olivia; Moake, Matthew M.
Abstract : Objectives: The aims of the study are to evaluate outcomes of esophageal bougienage for management of lodged esophageal coins and to assess the extent of bougienage usage and barriers among emergency providers. Methods: We performed a retrospective chart review of pediatric patients with single lodged esophageal coins presenting to our single academic pediatric emergency department between November 2012 and December 2018. We compared procedural outcomes, complications, length of stay (LOS), and cost between those managed with bougienage and with endoscopy. We further surveyed emergency physicians to assess the extent of bougienage usage and barriers to utilization across different institutions. Results: We identified 205 patients with single lodged esophageal coins presenting during our study window. One hundred forty-seven patients ultimately underwent bougienage with 97% success and no major complications. Fifty-six patients were managed by endoscopy with 100% success and one major complication. Bougienage had significantly lower LOS (median 2.18 vs 11.92 hours, P < 0.001) and hospital charges (median 3533 vs 12, 679, P < 0.001) compared with endoscopy. We received 242 completed surveys representing 38 states from primarily academic pediatric emergency physicians. The majority of respondents (90%) used specialist consult with only 4.5% performing bougienage. A total of 36.4% of respondents had never heard of the procedure and only 16.1% had ever performed it. Barriers to usage included lack of provider training (95.6%), perceived risk of complications (94.4%), and perceived lack of success (80.5%). Conclusions: Bougienage is safe and effective with significant LOS and cost benefits compared with endoscopy. Despite these advantages, the procedure is underused, because of lack of provider education and concerns regarding safety, efficacy, and both family and specialist preference, which are not supported by current literature. These data support the need for broader education regarding the bougienage technique, as well as larger prospective studies of its safety and outcomes.